2007
DOI: 10.1136/bmj.39231.599815.55
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotic Lactobacillus preparation to prevent diarrhoea associated with antibiotics: randomised double blind placebo controlled trial

Abstract: (2007) Use of probiotic Lactobacillus preparation to prevent diarrhoea associated with antibiotics: randomised double blind placebo controlled trial. British Medical Journal, 335 (7610).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
333
3
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(352 citation statements)
references
References 20 publications
5
333
3
11
Order By: Relevance
“…For instance, we learn from Siamon Gordon's account about Metchnikoff's interest and obsession with the gut flora and Metchnikoff's support for the use of lactobacilli. Probiotics are currently enjoying the limelight both from scientists and lay people, with new evidence from double-blind clinical trials supporting their usage for medicinal purposes [56]. Can we exploit the adaptive potential of macrophages to shape resistance to pathogens and degenerative diseases?…”
Section: From Phagocyte Biology To the Bedsidementioning
confidence: 99%
“…For instance, we learn from Siamon Gordon's account about Metchnikoff's interest and obsession with the gut flora and Metchnikoff's support for the use of lactobacilli. Probiotics are currently enjoying the limelight both from scientists and lay people, with new evidence from double-blind clinical trials supporting their usage for medicinal purposes [56]. Can we exploit the adaptive potential of macrophages to shape resistance to pathogens and degenerative diseases?…”
Section: From Phagocyte Biology To the Bedsidementioning
confidence: 99%
“…Th e environment is an important source of nosocomial infections ( 182,183 ). Interventions to reduce environmental contamination by C. diffi cile have decreased the incidence of infection, including a hypochlorite-based solution in a bone marrow transplant unit and ammonium compound cleaning agent in another study ( 184 -186 ( 187 ), but the study had small numbers of patients, excluded patients receiving high-risk antibiotics, and had a high rate of CDI in the placebo-treated patients. Another study reported that capsules containing Lactobacillus acidophilus CL1285 and L. casei LBC80R were eff ective in preventing both AAD and CDI in 255 hospitalized patients ( 188 ).…”
mentioning
confidence: 99%
“…396) in antibiotic-associated diarrhoea with S. boulardii and L. species in a meta-analysis of seven randomized controlled trials including 881 subjects. In a recent a randomized controlled trial on 135 hospitalized elderly subjects receiving antibiotic therapy, Hickson et al (17) reported a significant reduction of antibiotic-associated diarrhoea from 34 in the control group to 12 in the probiotic group (L. casei DN 114001) and, more strikingly, an absence of Clostridium difficile toxin in the stools of the probiotic group, while there were 17 positive samples in the control group. McFarland (18) confirmed, in a meta-analysis of six randomized controlled trials, a significant risk reduction (RR 0 .…”
Section: Demonstration Of the Impact Of Some Probiotics On The Defencmentioning
confidence: 99%